LEARNING MANAGEMENT SYSTEM (LMS) QUALITY METRICS: A CASE STUDY IN MALAYSIAN HIGHER LEARNING INSTITUTION - Mohamad Rosman , Mohamad Rahimi; Abdul Aziz , Mohammad Azhan; Razlan , Noor Masliana; Meida Rachmawati; Salamntu , Lumka (Journal of Islamic, Social, Economics and Development, 2024)
Learning management system is an information system specifically designed to manage the interaction between learners and educators. Education institutions throughout the world adopt different kinds of learning management system such as direct installation, open-source initiative, or customized version which are specifically tailored to the needs of the institutions. However, there is a lack of studies focusing on the metric’s quality of appraising the learning management system, as well as its impacts on individual satisfaction. Therefore, this study aims to develop the quality metrics in the context of a learning management system, and to investigate the relationship between the quality metrics of a learning management system and individual satisfaction. To address the research objectives, a quantitative study was conducted using an online questionnaire. Respondents were selected based on convenience sampling. The data was then analyzed based on descriptive and inferential analysis.